Analisis Pengaruh Variasi Debit Air (QL) dan Debit Gas (QG) terhadap Koefisien Transfer Oksigen (KLa) pada Performa Microbubble Generator - Mistoro, Niesa Hanum; Saraswati, Sri Puji; Ahmad, Johan Syafri Mahathir; Wiratni, Wiratni (Prosiding Seminar Nasional Teknik Kimia "Kejuangan", 2023)
The domestic wastewater treatment plant is usually installed using anaerobic system which has the disadvantage for low conversion process and large volume required. While the effectiveness of aerobic system can be increased by high consumption of energy to supply the oxygen. This study investigates the performance of Microbubble Generator (MBG) for wastewater treatment. The MBG utilizes the hydrodinamics of wastewater flow in the nozzle to provide energy-saving aeration. In this study, the clean water non-steady state test method was selected to find the overall oxygen transfer coefficient (KLa). The experiment was conducted by increasing the concentration of Dissolved Oxygen (DO) using MBG installed with submersible pump (water discharge, QL=80 l/min) and variations of gas discharge (QG) (0.15 l/min and 0.30 l/min). The KLa average results on QL 80 l/min at QG 0.15 l/min showed 0.01996/min and at QG 0.30 l/min showed 0.02564/min. These results indicate that the greater gas discharge (QG) can produce a greater KLa value. This happens because the more air is injected into the water and forms into micro-sized bubbles, the greater the rate of transfer oxygen to the liquid phase.